Effective numerical technique applied for Burgers' equation of (1 + 1)‐, (2 + 1)‐dimensional, and coupled forms. (14th April 2021) - Mohamed, Norhan A.; Rashed, Ahmed S.; Melaibari, Ammar; Sedighi, Hamid M.; Eltaher, Mohamed A.
Abstract : A numerical scheme based on backward differentiation formula (BDF) and generalized differential quadrature method (GDQM) has been developed. The proposed scheme has been employed to investigate three cases of Burgers' equation, one‐dimensional, two‐dimensional, and two‐dimensional coupled models. The results showed effectiveness accuracy in absolute error and error norms L 2 and L ∞ compared to other methods. The results were evaluated at different values of Reynold's number, Re, and viscosity, ν .